The Improvement of Teacher’s Organizational Commitment through Strengthening Servant Leadership with Trust as a Mediator - Sukarno, Sabar; Setyaningsih, Sri; Tukiran, Martinus (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
Teacher’s organizational commitment is crucial for achieving school goals. Teachers with high commitment to their schools can significantly positively impact both students and the overall school environment. This study explores the influence of servant leadership and trust on teacher’s organizational commitment, an area that has not been researched in the context of private Buddhist elementary schools. This research aims to analyze the direct and indirect relationships between servant leadership, trust, and teacher’s organizational commitment. The study employs a quantitative approach with path analysis techniques. The sample was drawn from a population of 355 permanent teachers from private Buddhist elementary schools in the Greater Jakarta area, resulting in a total of 189 respondents. Data were collected through questionnaires and analyzed using path analysis to test the proposed hypotheses. The results indicate that servant leadership (β = 0.314), and trust (β = 0.395) have a direct positive influence on teacher’s organizational commitment. Additionally, trust (β =0.262) serves as an significant intervening variable between servant leadership and teacher’s organizational commitment. The findings offer recommendations for schools and stakeholders as a strategy to improve teacher’s organizational commitment by strengthening servant leadership and trust.